Heard it in a love song - Garvis Graves, Tracey (St. Martin's Press, 2021)
"From Tracey Garvis Graves, the bestselling author of The Girl He Used to Know comes a love song of a story about starting over and second chances in Heard It in a Love Song. Love doesn't always wait until you're ready. Layla Hilding is thirty-five and recently divorced. Struggling to break free from the past-her glory days as the lead singer in a band and a ten-year marriage to a man who never put her first-Layla's newly found independence feels a lot like loneliness. Then there's Josh, the single dad whose daughter attends the elementary school where Layla teaches music. Recently separated, he's still processing the end of his twenty-year marriage to his high school sweetheart. He chats with Layla every morning at school and finds himself thinking about her more and more. Equally cautious and confused about dating in a world that favors apps over meeting organically, Layla and Josh decide to be friends with the potential for something more. Sounds sensible and way too simple-but when two people are on the rebound, is it heartbreak or happiness that's a love song away?"--